2015
DOI: 10.1515/pjvs-2015-0091
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of bovine leukemia virus in peripheral blood of Iranian cattle, camel and sheep

Abstract: Bovine leukemia virus (BLV) is a deltaretrovirus which infects and induces proliferation of B-lymphocytes in the peripheral blood circulation and in lymphoid organs primarily of cattle, leading to leukemia/lymphoma. This study was carried out to investigate the presence of BLV in cattle, sheep and camels from the Chaharmahal va Bakhtiary and Isfahan provinces in Iran. A total of 874 blood samples collected from cattle, sheep and camels were used in this study to detect BLV using a nested-PCR. The results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
4
10
0
2
Order By: Relevance
“…Viruses are one of the main causes of health problems, of which bovine leukemia virus (BLV) is one of the five agents considered most significant for cattle. In Colombia reported a seroprevalence per animal of 42.7% [1], which agreed with the reported worldwide with a range between 4 and 90% [2][3][4][5][6][7][8][9]. The disease is characterized by asymptomatic passage in 70% of infected animals, with persistent lymphocytosis developing in 30% and leukemia in 5% [10][11][12][13][14].…”
Section: Introductionsupporting
confidence: 75%
“…Viruses are one of the main causes of health problems, of which bovine leukemia virus (BLV) is one of the five agents considered most significant for cattle. In Colombia reported a seroprevalence per animal of 42.7% [1], which agreed with the reported worldwide with a range between 4 and 90% [2][3][4][5][6][7][8][9]. The disease is characterized by asymptomatic passage in 70% of infected animals, with persistent lymphocytosis developing in 30% and leukemia in 5% [10][11][12][13][14].…”
Section: Introductionsupporting
confidence: 75%
“…• Ovis aries (domestic sheep) (Green et al, 1988;Pannwitz et al, 1988;Kunakov and Abakin, 1993;Nekoei et al, 2015),…”
Section: Susceptible Animal Speciesmentioning
confidence: 99%
“… Ovis aries (domestic sheep) (Green et al., ; Pannwitz et al., ; Kunakov and Abakin, ; Nekoei et al., ), Vicugna pacos (Huacaya alpaca) (Lee et al., ). …”
Section: Assessmentmentioning
confidence: 99%
“…Epidemiological studies in Japan revealed varying levels of BLV prevalence throughout the country, based on different detection methods [ 83 , 134 136 ], and BLV infection rates of 40.9% of dairy and 28.7% of beef cattle, with infection rates in animals over 2-years-old reaching 78% in dairy herds and 69% in beef cattle herds [ 136 ]. Less than 6% of cattle were infected with BLV in Mongolia (3.9%) [ 77 ], Cambodia (5.3%) [ 137 ], and Taiwan (5.8%) [ 48 ], while a serological survey in Iran revealed that the prevalence of BLV was between 22.1% and 25.4% in that country [ 138 , 139 ]. Lee et al [ 102 ] demonstrated an average prevalence of BLV of 58.7% in Thailand, reaching maxima of 87.8% and 100% of cattle when assayed using PCR and ELISA, respectively.…”
Section: Introductionmentioning
confidence: 99%